2016
DOI: 10.1016/j.kint.2016.01.014
|View full text |Cite
|
Sign up to set email alerts
|

Advanced chronic kidney disease populations have elevated trimethylamine N-oxide levels associated with increased cardiovascular events

Abstract: Cardiovascular disease is more common in patients with chronic kidney disease (CKD), and traditional risk factors do not adequately predict those at risk for cardiovascular (CV) events. Recent evidence suggests elevated trimethylamine N-oxide (TMAO), created by gut microflora from dietary L-carnitine and choline, is associated with CV events. We investigated the relationship of TMAO levels in patients with stages 3b and 4 CKD to ischemic CV events using the CanPREDDICT cohort, a Canada-wide observational study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
104
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 149 publications
(112 citation statements)
references
References 29 publications
8
104
0
Order By: Relevance
“…3437 In a cross-sectional analysis, serum TMAO concentrations were found to correlate with atherosclerotic burden among 220 individuals with CKD who had undergone coronary angiography, and in exploratory analysis appeared to be associated with long-term mortality. 35 Similarly, in an independent cohort of 179 individuals with CKD, higher TMAO was associated with all-cause mortality.…”
Section: Overview Of the Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…3437 In a cross-sectional analysis, serum TMAO concentrations were found to correlate with atherosclerotic burden among 220 individuals with CKD who had undergone coronary angiography, and in exploratory analysis appeared to be associated with long-term mortality. 35 Similarly, in an independent cohort of 179 individuals with CKD, higher TMAO was associated with all-cause mortality.…”
Section: Overview Of the Literaturementioning
confidence: 99%
“…36 In the largest CKD study to date, investigators used LC-MS to measure plasma TMAO, choline, and L-carnitine in 2529 individuals with stage 3b/4 CKD and found that TMAO was independently associated with CV events (HR per SD 1.23, P < 0.006) during 3 years follow-up. 37 The association between TMAO and CV outcomes in ESRD has been less consistent. For example, in one study of 235 incident hemodialysis patients, baseline TMAO levels were not associated with time to death, cardiovascular hospitalization, or cardiovascular death.…”
Section: Overview Of the Literaturementioning
confidence: 99%
“…37 Finally, in a large study of over 2500 Canadian patients with CKD, plasma TMAO independently predicted CV events over a 3-year follow-up period in stage 3, but not in stage 4 (in which TMAO was much more variable). 39 Some thought is required before interpreting these data as evidence of an independent association between TMAO and CV disease in renal impairment, let alone one of causation. Statistical correction for reduced renal clearance of TMAO using creatinine or cystatin C -based measures of eGFR does not account for tubular function, which has an impact on excretion of TMAO.…”
Section: Tmao and CV Risk In Chronic Kidney Diseasementioning
confidence: 99%
“…Chronic kidney disease (CKD) patients who undergo hemodialysis are at risk for secondary carnitine deficiency because hemodialysis removes carnitine from the blood. While CVD is known as one of the major cause of death in CKD patients, the association between plasma TMAO level and CVD risk in CKD is debated (Kim et al, 2016; Stubbs et al, 2016; Tang et al, 2015). Overall, while TMAO derived from endogenous and exogenous sources of choline and carnitine may contribute to increased atherosclerotic vascular disease, red meat does not appear to be a major source of this compound, relative to other foods.…”
Section: Existing Theories To Explain Increased Disease Risks Of Rmentioning
confidence: 99%